Nitrogen immobilization in leaf litter at two Mediterranean ecosystems of SW Spain (Biogeochemistry, 1992)
Nitrogen immobilization in relation to the dynamics of lignin and tannins in nine different types of leaf litter was investigated during a 2-yr study at two Mediterranean ecosystems of SW Spain. Net nitrogen immobilization for all the species was higher in a forest than in the more nutrient-poor soil of a shrubland. Absolute amount of lignin increased in both ecosystems in the first 2-4 months whereas tannin rapidly decreased in the same time period. Increases in lignin were significantly correlated to losses of tannins during decomposition. Initial tannin content was the best predictor of the maximum amount of immobilized nitrogen in litter in both ecosystems. Mechanisms that could explain the immobilization of nitrogen in litter are discussed.